Intravenous Iron Dosing and Infection Risk in Patients on Hemodialysis: A Prespecified Secondary Analysis of the PIVOTAL Trial - Macdougall, Iain C.; Bhandari, Sunil; White, Claire; Anker, Stefan D.; Farrington, Kenneth; Kalra, Philip A.; Mark, Patrick B.; McMurray, John J. V.; Reid, Chante; Robertson, Michele; Tomson, Charles R.V.; Wheeler, David C.; et al. (Journal of the American Society of Nephrology, 2020)
Experimental and observational studies have raised concerns that giving intravenous (IV) iron to patients, such as individuals receiving maintenance hemodialysis, might increase the risk of infections. The Proactive IV Iron Therapy in Haemodialysis Patients (PIVOTAL) trial randomized 2141 patients undergoing maintenance hemodialysis for ESKD to a high-dose or a low-dose IV iron regimen, with a primary composite outcome of all-cause death, heart attack, stroke, or hospitalization for heart failure. Comparison of infection rates between the two groups was a prespecified secondary analysis. Secondary end points included any infection, hospitalization for infection, and death from infection; we calculated cumulative event rates for these end points. We also interrogated the interaction between iron dose and vascular access (fistula versus catheter). We found no significant difference between the high-dose IV iron group compared with the lose-dose group in event rates for all infections (46.5% versus 45.5%, respectively, which represented incidences of 63.3 versus 69.4 per 100 patient years, respectively); rates of hospitalization for infection (29.6% versus 29.3%, respectively) also did not differ. We did find a significant association between risk of a first cardiovascular event and any infection in the previous 30 days. Compared with patients undergoing dialysis with an arteriovenous fistula, those doing so a catheter had a higher incidence of having any infection, hospitalization for infection, or fatal infection, but IV iron dosing had no effect on these outcomes. The high-dose and low-dose IV iron groups exhibited identical infection rates. Risk of a first cardiovascular event strongly associated with a recent infection.